NON-MUSLIM LEADERSHIP POLEMIC IN INDONESIA: Outcomes of Muktamar NU XXX at Lirboyo in 1999 and Bahtsul Masail Kiai Muda Ansor in 2017 - Bahri, Syaiful (IAIN Tulungagung, 2018)
Non-Muslim leadership is still being a political issue and causes polemic in Indonesia. The previous election of Governor of DKI Jakarta was remembering last controversy either probability or prohibition to vote a non-muslim as a chief. The law judgments addressing this issue are NU Congress at Lirboyo in 1999 and Bahtsul Masail Kiai Muda GP Ansor in 2017. According to Congress at Lirboyo, authorizing state affairs to a non-Muslim is not allowed, except in an emergency situation. Meanwhile, Bahtsul Masailof Kiai Muda Ansor in 2017 decided that voting non-Muslim leader in Indonesia is legally and constitutionally legitimate. This paper is trying to examine istinbat method which is used in those two forums considering their position in the theory of al-Sabit and al-Mutahawwil. By conducting a literature study, the author concludes that the outcomes of Muktamar NUat Lirboyo in 1999 using the istinbat Bayani method, belongs to al-Sabit category. Meanwhile, the outcomes of Bahtsul Masail Kiai Muda GP Ansor in 2017 which is using a combination of istinbat Bayani and istislahi, belongs to an al-Mutahawwil category.